Crystal Structure of the Monomeric Extracellular Domain of α9 Nicotinic Receptor Subunit in Complex With α-Conotoxin RgIA: Molecular Dynamics Insights Into RgIA Binding to α9α10 Nicotinic Receptors - Zouridakis, Marios; Papakyriakou, Athanasios; Ivanov, Igor A.; Kasheverov, Igor E.; Tsetlin, Victor; Tzartos, Socrates; Giastas, Petros (Frontiers in Pharmacology, 2019)
The α9 subunit of nicotinic acetylcholine receptors (nAChRs) exists mainly in heteropentameric assemblies with α10. Accumulating data indicate the presence of three different binding sites in α9α10 nAChRs: the α9(+)/α9(-), the α9(+)/α10(-) and the α10(+)/α9(-). The major role of the principal (+) side of the extracellular domain (ECD) of α9 subunit in binding of the antagonists methyllylcaconitine and α-bungarotoxin was shown previously by the crystal structures of the monomeric α9-ECD with these molecules. Here we present the 2.26-Å resolution crystal structure of α9-ECD in complex with α-conotoxin (α-Ctx) RgIA, a potential drug for chronic pain, the first structure reported for a complex between an nAChR domain and an α-Ctx. Superposition of this structure with those of other α-Ctxs bound to the homologous pentameric acetylcholine binding proteins revealed significant similarities in the orientation of bound conotoxins, despite the monomeric state of the α9-ECD. In addition, ligand-binding studies calculated a binding affinity of RgIA to the α9-ECD at the low micromolar range. Given the high identity between α9 and α10 ECDs, particularly at their (+) sides, the presented structure was used as template for molecular dynamics simulations of the ECDs of the human α9α10 nAChR in pentameric assemblies. Our results support a favorable binding of RgIA at α9(+)/α9(-) or α10(+)/α9(-) rather than the α9(+)/α10(-) interface, in accordance with previous mutational and functional data.